2017
DOI: 10.1111/pbi.12632
|View full text |Cite
|
Sign up to set email alerts
|

Aldo‐keto reductase enzymes detoxify glyphosate and improve herbicide resistance in plants

Abstract: SummaryIn recent years, concerns about the use of glyphosate‐resistant crops have increased because of glyphosate residual levels in plants and development of herbicide‐resistant weeds. In spite of identifying glyphosate‐detoxifying genes from microorganisms, the plant mechanism to detoxify glyphosate has not been studied. We characterized an aldo‐keto reductase gene from Pseudomonas (PsAKR1) and rice (OsAKR1) and showed, by docking studies, both PsAKR1 and OsAKR1 can efficiently bind to glyphosate. Silencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 39 publications
2
43
0
1
Order By: Relevance
“…Codeinone reductases display the conserved AKR catalytic tetrad (D51, Y56, K86, H119) and mediate activity via an α/β barrel motif binding NADP(H) (Jez et al ., ). Plant AKRs play diverse physiological roles including in defense and the stress response, biosynthesis of osmolytes and membrane transport (Tang et al ., ; Kanayama et al ., ; Turóczy et al ., ; Vemanna et al ., ). Currently, COR and 1,2‐dehydroreticuline reductase (DRR) are the two known AKRs involved in BIA metabolism (Unterlinner et al ., ; Farrow et al ., ; Winzer et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Codeinone reductases display the conserved AKR catalytic tetrad (D51, Y56, K86, H119) and mediate activity via an α/β barrel motif binding NADP(H) (Jez et al ., ). Plant AKRs play diverse physiological roles including in defense and the stress response, biosynthesis of osmolytes and membrane transport (Tang et al ., ; Kanayama et al ., ; Turóczy et al ., ; Vemanna et al ., ). Currently, COR and 1,2‐dehydroreticuline reductase (DRR) are the two known AKRs involved in BIA metabolism (Unterlinner et al ., ; Farrow et al ., ; Winzer et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…This AKR protein has little similarity to GOX and Gly oxidase of microbes that generate AMPA and glyoxylate from glyphosate. Vemanna et al (2017) had already shown that overexpression of transgenes of Pseudomonas and rice encoding AKR provides glyphosate resistance in tobacco (Nicotiana tabacum), and that silencing or mutating AKR genes in both plants and microbes increased sensitivity to glyphosate. These findings provided the clue that evolution of enhanced expression of an AKR gene in a weed could provide glyphosate resistance.…”
mentioning
confidence: 99%
“…b). Another study suggested that overexpressing aldo‐keto reductase enzymes in rice and tobacco could enhance glyphosate tolerance possibly through metabolism . However, the evolution of glyphosate metabolism in plants is rare and has been reported for only a few plants such as soybean, and the possibility of whether or not metabolism contributes to evolved glyphosate resistance in weeds remains to be proven …”
Section: Resultsmentioning
confidence: 99%